Stimulation of heme oxygenase in macrophages and liver by endotoxin. - Gemsa, D (1974)
In rat peritoneal macrophages, engaged in erythrophagocytosis in vitro, endotoxin stimulated heme oxygenase (HO) activity, which was additive to the substrate-mediated enzyme induction produced by the ingested erythrocyte hemoglobin. Endotoxin neither appeared to injure the erythrocytes, nor did it enhance the rate of erythrophagocytosis. In intact rats, HO activity in both parenchymal and sinusoidal cells of the liver was increased after treatment with endotoxin. It is likely that endotoxin directly stimulates HO activity, a process which may account for the reported rise in bilirubin formation in endotoxin-treated animals. The effect of endotoxin on HO may represent part of the general activation of phagocytic cells by endotoxin.